2021
DOI: 10.21203/rs.3.rs-151696/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association Between Glycemic Gap and Mortality in Critically Ill Patients with Diabetes

Abstract: Objectives: Dysglycemia is pervasive and associated with poor outcomes in critically ill patients. Hyperglycemia, hypoglycemia and blood glucose fluctuation might all affect the outcomes, but appropriate level of blood glucose is uncertain especially in patients with diabetes regarding to the situation of glucose control before hospitalization. This study was aimed to investigate the effect of difference between mean blood glucose during ICU stay and level of blood glucose prior to admission to ICU upon outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…21 The conclusion above impelled us to implement a more rational and effective protocols to monitor and control blood glucose to avoid or balance the two extremes which were “uncontrolled hyperglycemia” and “over tightly controlled glucose. 22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The conclusion above impelled us to implement a more rational and effective protocols to monitor and control blood glucose to avoid or balance the two extremes which were “uncontrolled hyperglycemia” and “over tightly controlled glucose. 22…”
Section: Discussionmentioning
confidence: 99%
“…21 The conclusion above impelled us to implement a more rational and effective protocols to monitor and control blood glucose to avoid or balance the two extremes which were "uncontrolled hyperglycemia" and "over tightly controlled glucose. 22 Tangible proof convinced researchers of the fact that hyperglycemia of critically ill patients could not totally attribute to stress response. 23 It makes researchers turn to the relationship between the degree of premorbid glycaemia and mortality, the admission blood glucose levels are especially proved associated with higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This might be the reason why studies fail to replicate the benefit of tight glycemic control on ICU mortality 36 . The above conclusion leads us to implement a more rational and effective protocol to monitor and control the level of blood glucose to avoid or balance the two extremes which are ‘uncontrolled hyperglycemia’ and ‘over tightly controlled glucose’ 37 . Therefore, hypoglycemia may indicate the severity of acute illnesses and it seems prudent to prevent long‐lasting hypoglycemia as much as possible by frequent and accurate blood glucose measurements and by the use of a proper insulin protocol with safe and rational blood glucose range.…”
Section: Discussionmentioning
confidence: 99%
“…Although Glucose_max reflects the patient’s acute response under stress, if the Glucose_max value is in the abnormal range, then blood glucose management is ineffective 22 . An increasing number of studies have proven that strengthening blood sugar control can reduce the in-hospital mortality risk of patients 23 25 . According to our prediction, the overall trend of the correlation between Glucose_max and in-hospital mortality should be similar to that between Glucose_mean and in-hospital mortality; however, because the number of patients who had Glucose_max levels in the hypoglycemic range in this study was extremely small, it only showed an upward trend.…”
Section: Discussionmentioning
confidence: 99%